Police Authority In Handling Corruption Crimes Under Law No. 2 Of 2002 Concerning State Police Of The Republic Of Indonesia - Rosadi, Herry; Muhibbin, Moh.; Arief, Hanafi (International Journal of Law, Environment, and Natural Resources, 2023)
The criminal act of corruption is a latent danger for Indonesia because the negative impacts and the causes are very dangerous for the economy and social order. This research aims to determine the regulation of the authority of law enforcement agencies in handling criminal acts of corruption in the legal system in Indonesia and how the authority of the police in handling criminal acts of corruption in Indonesia. As normative legal research, the research examines laws and regulations related to criminal acts of corruption.Research results: Regulation of criminal acts of corruption in Indonesia is regulated in the Corruption Eradication Law Number 20 of 2001, and Law Number 8 of 1981 concerning the Criminal Procedure Code. The Criminal Procedure Code only recognizes 2 institutions or agencies that have the authority to handle criminal acts, namely the Police and the Prosecutor's Office. In Law Number 20 of 2001, the investigative authority is contained in the institutions that have the authority to handle criminal acts of corruption, namely the Police, Prosecutor's Office and the Corruption Eradication Commission. Law Number 2 of 2002 concerning the National Police of the Republic of Indonesia, aims to strengthen the position and role of the police as an integral part of overall reform efforts. The development and progress of society as well as the emergence of the supremacy of law, globalization, transparency and accountability have given rise to a new perspective on the duties, functions, authority and responsibilities of the police which has led to the growth of various demands and expectations from the public regarding the implementation of police duties oriented towards the interests of the community.